THE DEVELOPMENT OF SOCIAL STUDIES TEACHING MATERIALS BASED ON MALAY SIAK SONGKET WEAVING FOR FOURTH GRADE ELEMENTARY SCHOOL STUDENTS - Guslinda Guslinda; Rita Kurnia; Munjiatun Munjiatun (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
Growing awareness of students to love their own culture is not easy, there needsto be an effort to introduce. Culture-oriented learning supported by relevant teaching materials is an articative to the answer. The purpose of this research is the development of  IPS elementary teaching material  based on  Siak Malay songket weaving. It is expected that with the development of teaching materials students will develop a love for their own culture, especially about the weaving of Malay Siak songket and can also increase learning activities. Teaching material products  can be used in social studies learning for fourth grade elementary school students, especially on the theme of "The beauty of togetherness" with the sub-theme of "cultural diversity of my people". This research used research and development or R&D method with a 4-D model, which consisted of four stages, namely: (1) Define; (2) Design and; (3) Develop, and (4) Disseminate. The results showed that the development of teaching materials that have been developed are feasible to be used and are also practical. This was evidenced by the validity of teaching materials seen from: 1) the feasibility of the contents of 93.7 2) the language convention of 93.7 3) the presentation of 87.5 and 4) the 86 graphics, which obtained an average score of 90.2. while for practicality which was seen from the response of students obtained each statement was in the range of 75 to 93.75 which was included in the category of practical and very practical thus the practicality percentage of 87.5. Then it can be concluded that the development of teaching materials  is feasible and practical to be used for elementary social studies learning in grade IV primary schools.